2021
DOI: 10.3390/ijms222212466
|View full text |Cite
|
Sign up to set email alerts
|

Over Fifty Years of Life, Death, and Cannibalism: A Historical Recollection of Apoptosis and Autophagy

Abstract: Research in biomedical sciences has changed dramatically over the past fifty years. There is no doubt that the discovery of apoptosis and autophagy as two highly synchronized and regulated mechanisms in cellular homeostasis are among the most important discoveries in these decades. Along with the advancement in molecular biology, identifying the genetic players in apoptosis and autophagy has shed light on our understanding of their function in physiological and pathological conditions. In this review, we first… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 520 publications
(546 reference statements)
0
9
0
Order By: Relevance
“…Apoptosis is a Caspase-dependent cell death that includes intrinsic pathways induced by DNA damage, ROS accumulation, and endoplasmic reticulum stress (also known as the mitochondrial pathway) as well as exogenous apoptotic pathways initiated by the binding of other cellular soluble or cell surface ligands including TNF, FasL, or TRAIL to death receptors ( 95 ). The Caspase family is a family of evolutionarily conserved cysteine-dependent endonucleases that are primarily involved in cell death and inflammatory responses.…”
Section: Different Types Of Pcd and Lipid Metabolism In Macrophagesmentioning
confidence: 99%
“…Apoptosis is a Caspase-dependent cell death that includes intrinsic pathways induced by DNA damage, ROS accumulation, and endoplasmic reticulum stress (also known as the mitochondrial pathway) as well as exogenous apoptotic pathways initiated by the binding of other cellular soluble or cell surface ligands including TNF, FasL, or TRAIL to death receptors ( 95 ). The Caspase family is a family of evolutionarily conserved cysteine-dependent endonucleases that are primarily involved in cell death and inflammatory responses.…”
Section: Different Types Of Pcd and Lipid Metabolism In Macrophagesmentioning
confidence: 99%
“…Apoptosis, a programme of controlled cell death [ 434 ], may have a role in the neuronal cell death associated with AD, based on evidence of increased apoptosis in the AD brain compared with the normal brain [ 435 , 436 ]. 25 plant species in this study had reports of anti-apoptotic bioactivity (Additional file 4 : Table S4).…”
Section: Resultsmentioning
confidence: 99%
“…44 Proteolytic activation of Caspase 3 triggers cascade activation of caspases, predominantly Caspase 9 , thereby initiating apoptosis. 45 Moreover, Bcl-2 and its relatives can also regulate apoptosis in response to Caspase 3 activation. 46,47 Previous studies have shown that ETEC infection leads to increased apoptosis of the intestinal epithelial cells, which will contribute to the disruption of the intestinal epithelium.…”
Section: Discussionmentioning
confidence: 99%
“…44 Proteolytic activation of Caspase 3 triggers cascade activation of caspases, predominantly Caspase 9, thereby initiating apoptosis. 45 Moreover, Bcl-2 and its relatives can also regulate apoptosis in response to Caspase 3 activation. 46,47 Previous studies have shown that ETEC infec-…”
Section: Papermentioning
confidence: 99%